2000
DOI: 10.1103/physrevlett.84.3398
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Photon-Assisted Noise in a Diffusive Normal Metal–Superconductor Junction

Abstract: We report measurements of nonequilibrium noise in a diffusive normal metal-superconductor (N-S) junction in the presence of both dc bias and high-frequency ac excitation. We find that the shot noise of a diffusive N-S junction is doubled compared to a normal diffusive conductor. Under ac excitation of frequency nu the shot noise develops features at bias voltages |V| = hnu/(2e), which bear all the hallmarks of a photon-assisted process. Observation of these features provides clear evidence that the effective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
135
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 20 publications
9
135
3
Order By: Relevance
“…Thus, in this process a charge transfer of 2e occurs, but with a reduced probability, since two particles have to tunnel. The shot noise is proportional to the charge of the elementary processes, and one thus naivly expects a doubling of the shot noise, which was indeed found theoretically [12,13] and experimentally [14,15] for diffusive conductors. It is remarkable that this doubling occurs for diffusive conductors, whereas it is not found for other conductors like, e. g., single-channel contacts [3,12,[16][17][18] , double tunnel junctions [19][20][21][22], or diffusive junctions with a tunneling barrier [23,24].…”
Section: Introductionmentioning
confidence: 89%
“…Thus, in this process a charge transfer of 2e occurs, but with a reduced probability, since two particles have to tunnel. The shot noise is proportional to the charge of the elementary processes, and one thus naivly expects a doubling of the shot noise, which was indeed found theoretically [12,13] and experimentally [14,15] for diffusive conductors. It is remarkable that this doubling occurs for diffusive conductors, whereas it is not found for other conductors like, e. g., single-channel contacts [3,12,[16][17][18] , double tunnel junctions [19][20][21][22], or diffusive junctions with a tunneling barrier [23,24].…”
Section: Introductionmentioning
confidence: 89%
“…Eq. (7) constitutes the starting point for computing both finite frequency noise and the zero frequency noise in the presence of a local harmonic perturbation, such as in the Non Stationary AB effect in NS junctions 7 which was recently detected experimentally 6 . Here it constitutes the starting point for the computation of the density-density correlator, and it is valid both in the Andreev regime and above gap, provided that the proper distribution functions are specified on the superconducting side.…”
Section: Current and Density Fluctuationsmentioning
confidence: 99%
“…In the Andreev regime, at zero temperature, it is expected that the calculation of the decoherence rate is similar to that of a normal metal point contact except that the charge of the carriers is replaced by the Cooper pair charge 6 . This simple analogy fails both at finite temperatures and at voltage biases superior to the superconducting gap.…”
Section: Introductionmentioning
confidence: 99%
“…(7), calculating the corresponding T N (x i ) by means of (2) and averaging them over the corresponding segments, one easily obtains that T 1 = T 3 = eV /6 and T 2 = T 4 = eV /4. From this, one readily obtains the cross-correlated spectral densities by means of (6). Taking into account that the average current flowing between the normal electrodes is I = eV /2R, the expression for the noise at the normal ends may be written in the form…”
mentioning
confidence: 99%
“…2,3 This doubling was interpreted as an effective doubling of electron charge and has been experimentally confirmed in a number of papers. [4][5][6] Quite recently, it was shown that the doubled shot noise in diffusive NS contacts survives at finite voltages of the order of the energy gap. 7 Moreover, this noise does not require a phase coherence 8 and may be described in terms of a semiclassical Boltzmann -Langevin equation.…”
mentioning
confidence: 99%